Scientific Opinion on the substantiation of a health claim related to Bimuno® GOS and reducing gastro‐intestinal discomfort pursuant to Article 13(5) of Regulation (EC) No 1924/2006 - EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) (EFSA journal, 2014)
Following an application from Clasado Limited, submitted for authorisation of a health claim pursuant to Article 13(5) of Regulation (EC) No 1924/2006 via the Competent Authority of Malta, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to deliver an opinion on the scientific substantiation of a health claim related to Bimuno® GOS and reducing gastro‐intestinal discomfort. The food constituent that is the subject of the health claim, Bimuno® GOS, which is a mixture of β‐galacto‐oligosaccharides produced through conversion of lactose by enzymes from Bifidobacterium bifidum NCIMB 41171, is sufficiently characterised. The claimed effect is reducing gastro‐intestinal discomfort and is considered to be a beneficial physiological effect. The applicant did not provide any studies from which data could be used for the scientific substantiation of the claimed effect of reducing gastro‐intestinal discomfort. A cause and effect relationship has not been established between the consumption of Bimuno® GOS and reducing gastro‐intestinal discomfort.